Fabrication of SERS Substrates Based on Porous- Si Nanostructures and Silver Nanoparticles for Application in Identification of Carbendazim - Duy Thien, Nguyen; Thi Cuc, Than; Van Hiep, Vuong; Van Vu, Le (VNU Journal of Science: Mathematics - Physics, 2022)
In this work, we present a quick and simple approach for fabrication of active-surface-enhanced Raman scattering (SERS) substrates based on silver nanoparticles (AgNPs) and porous silicon nanostructures (denoted by Si/Ag substrate). SERS substrates were fabricated by a 3-stage-process including the deposition of Au nanoparticles on Si wafer, etching for porous Si wafer, and coating Ag NPs on porous Si to produce SERS-active layer. To control the uniformity and cleanliness of the SERS substrate, sputtering technique was used to coat Au and AgNPs. The absorption spectra of the Si/Ag substrates exhibited a strong surface plasmon resonance absorption band of AgNPs at 425 nm. Using Si/Ag substrates to detect carbenzadim (CBZ) residue dispersed in acetone has shown that Si/Ag substrates morphology greatly affected the Raman intensity of carbendazim which opens up a promising and potential approach using SERS spectroscopy for food, environment and especially pharmaceutical applications. Keywords: Raman, SERS, plasmon, nanoparticles, carbendazim.